Women in Chiapas : making history in times of struggle and hope - Eber, Christine Engla; Kovic, Christine Marie (Routledge, 2003)
This book presents the concerns, visions and struggles of women in Chiapas, Mexico in the context of the uprising of the Zapatista Army of National Liberation (EZLN). The book is organized around three issues that have taken center state in women's recent struggles-structural violence and armed conflict; religion and empowerment and women's organizing. Also includes maps.